Electrospinning of Poly(1, 4‐Cyclohexanedimethylene Acetylene Dicarboxylate): Study on the Morphology, Wettability, Thermal and Biodegradation Behaviors. Issue 23 (13th November 2020) - Daglar, Ozgun; Altinkok, Cagatay; Acik, Gokhan; Durmaz, Hakan
Abstract: This study is conducted to evaluate the biodegradation and thermal features of poly(1, 4‐cyclohexanedimethylene acetylene dicarboxylate) (PCA) based films and fibers. The PCA is characterized by Fourier transform infrared (FT‐IR) and proton nuclear magnetic resonance ( 1 H‐NMR) spectroscopies and gel permeation chromatography (GPC). The beadless fibers of PCA are achieved by electrospinning from its solution under ambient conditions for the first time. The effects of applied voltage and tip‐to‐collector distance (TCD) on the various properties such as morphology, wettability, thermal, and biodegradability behaviors of fibers are investigated by comparing the non‐electrospun PCA. Morphologies and average frequency distributions of the electrospun samples are elucidated by scanning electron microscopy (SEM). Wettability properties of the studied samples are determined by water contact angle (WCA) measurements, whereas thermo‐stabilities and glass transition temperatures ( T g ) are established by thermogravimetric and differential scanning calorimetry analyses (TGA and DSC), respectively. Biodegradation studies indicate that 28% of electrospun PCA achieved at 8 mL h −1 flow rate, 20 cm TCD and 25 kV applied voltage can be enzymatically degraded within 15 days. It is thus estimated that PCA with good electrospun and biodegradation abilities will favorable candidates for bio‐polyester applications. Abstract : Biodegradable electrospun poly(1, 4‐cyclohexanedimethylene acetylene dicarboxylate) (PCA) having internal alkyne units is achieved. Smooth, cylindrical, and bead‐free microfibers of PCA are obtained. The effect of different electrospinning parameters on the morphological, wettability, thermal, and biodegradation features of electrospun PCAs are thoroughly investigated. Degradation rate of both electrospun PCAs and assynthesized PCA is higher in enzymatic testing conditions compared to hydrolytic medium.